2018
DOI: 10.1111/aos.13935
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone for unresponsive diabetic macular oedema: optical coherence tomography biomarkers

Abstract: Purpose To analyse the effects of intravitreal dexamethasone implant (DEX) in patients with diabetic macular oedema (DME) unresponsive to ranibizumab treatment, in relation to the inflammatory optical coherence tomography (OCT) retinal features, subfoveal neuroretinal detachment (SND) and hyperreflective retinal spots (HRS). Methods Patients with DME poorly responsive to three injections of ranibizumab were treated with DEX. Best‐corrected visual acuity (BCVA) and central macula thickness (CMT, measured by Spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 28 publications
0
51
0
1
Order By: Relevance
“… 29 These HRS have peculiar features, such as dimension <3 0 μm, reflectivity similar to that of the nerve fiber layer, absence of back-shadowing, and location in both the inner and outer retina. 29 Previous studies have demonstrated a decrease in the number of HRS after treatment with both intravitreal dexamethasone and anti-VEGF drugs 23 , 30 , 31 ; however, no evidence has been reported so far regarding the effect of SMPL on HRS during long-term follow-up. In this study, a progressive decrease in the number of HRS was documented up to 1 year after treatment with SMPL.…”
Section: Discussionmentioning
confidence: 99%
“… 29 These HRS have peculiar features, such as dimension <3 0 μm, reflectivity similar to that of the nerve fiber layer, absence of back-shadowing, and location in both the inner and outer retina. 29 Previous studies have demonstrated a decrease in the number of HRS after treatment with both intravitreal dexamethasone and anti-VEGF drugs 23 , 30 , 31 ; however, no evidence has been reported so far regarding the effect of SMPL on HRS during long-term follow-up. In this study, a progressive decrease in the number of HRS was documented up to 1 year after treatment with SMPL.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with uveitic cystoid ME, DEX implant was able to reverse outer retinal layer alterations [29]. These findings were also observed in patients with ME associated with branch retinal vein occlusion (BRVO) [17, 30]. Moreover, it was suggested that DEX implant may recover morphology of outer retinal layer in patients with DME, which might be associated with better functional outcomes [13, 17, 31].…”
Section: Introductionmentioning
confidence: 99%
“…The relevance of these findings critically depends on whether early retina recovery will be associated with better functional outcomes. Since most of the evidence has evaluated the effect of DEX implant on ELM and EZ integrity in previously treated patients [13, 17, 28, 29, 31], it might be interesting to know what happens in treatment-naïve patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations